Evolutionary differences in executive neuropsychological functions in children from Lima and Ayacucho - Canales Gabriel, Ricardo C. (2022)
The study of executive functions is a subject that arouses the interest of researchers in neuropsychology and neuroscience. In particular, the evolutionary aspects of these neuropsychological functions, in an effort to be able to identify the way in which these functions appear in the child and how they take shape in adolescence, is a topic under exploration. The present investigation sought to determine if there were differences in the evolution of executive functions in children differentiated in age groups: 6-7 years, 8-9 years, 10-12 years. For this, the Battery of executive functions was used: BANFE 2, by Flores, Ostrosky and Lozano (2014). This is a basic research with a comparative descriptive design. The results showed significant differences in working memory and executive functions according to age range. This is particularly appreciated in the functions of Visuospatial Working Memory, Planning, Mental Flexibility, Verbal Fluency and Sequential Planning and Strategy Formulation. In the set of executive neuropsychological functions examined, students in the age group 10 to 12 years were the ones who obtained the highest scores. No statistically significant differences were found when comparing the performance in working memory and executive functions of the students taking into account their origin, whether from Lima or Ayacucho.